Anthropometric profile and perception of quality of life of women suffered with breast cancer after chemotherapy treatment (Research, Society and Development, 2023)
Breast cancer is the most common form of cancer affecting women worldwide, representing a significant public health challenge. Several types of treatments are available to combat this disease, with an emphasis on systemic treatment, including hormone therapy and chemotherapy. However, these treatments often have side effects that impact appetite and lead to weight gain. Therefore, the objective of this study focused on analyzing how women diagnosed with breast cancer perceive their quality of life and how their anthropometric profile is affected after completing chemotherapy treatment. For this investigation, we adopted a descriptive and analytical approach, combining qualitative and quantitative elements. Two questionnaires were administered to the participants: the QLQ-BR23 questionnaire from the European Organization for Research and Treatment of Cancer (EORTC) and another designed specifically by the researchers to assess the participants' perception of quality of life. The results revealed that the majority of participants were overweight according to anthropometric assessment. In addition, many reported symptoms such as fatigue, lack of energy and anxiety. In the QLQ-BR23 questionnaire, it was noted that body image was one of the main points of concern in terms of functional scale, while systemic symptoms received more complaints in the symptoms category. These findings suggest that chemotherapy treatment has a lasting impact on patients' quality of life after its completion, highlighting the need for additional investigations on the subject.